Interactions of environmental conditions and mechanical loads have influence on matrix turnover by nucleus pulposus cells. - Neidlinger-Wilke, C; Mietsch, A; Rinkler, C; Wilke, H; Ignatius, A; Urban, J (2012)
Disc degeneration is associated with several changes in the physicochemical environment of intervertebral disc cells. Nucleus pulposus (NP) cells in the center of degenerated discs are exposed to decreased glucose supply, osmolarity, pH, and oxygen levels. To understand the complexity of these interactions on a cellular level, we designed standardized experiments in which we compared responses to these environmental factors under normal levels with those seen under two different degrees of disc degeneration. We hypothesized that these changes in environmental stimuli influence gene expression of matrix proteins and matrix degrading enzymes and alter their responses to cyclic hydrostatic pressure (HP). Our results suggest that a simulation of degenerative conditions influences the degradation of disc matrix through impairing matrix formation and accelerating matrix resorption via up- or down-regulation of the respective target genes. The greatest effects were seen for decreases in glucose concentration and pH. Low oxygen had little influence. HP had little direct effect but appeared to counteract matrix degradation by reducing or inverting some of the adverse effects of other stimuli. For ongoing in vitro studies, interactions between mechanical stimuli and factors in the physicochemical environment should not be ignored as these could markedly influence results.